A Study of Differences in Penile Dorsal Nerve Somatosensory Evoked Potential Testing Among Healthy Controls and Patients with Primary and Secondary Premature Ejaculation. Issue 4 (18th March 2021) - Sun, Zhaohui; Liao, Zedong; Zheng, Qigang; Chen, Jiajian; Lv, Bodong; Bao, Chunxiang; Huang, Xiaojun
ABSTRACT: Background: Penile dorsal nerve somatosensory evoked potential (DNSEP) is a scientific and objective technique that provides effective and objective data to establish the diagnosis of premature ejaculation (PE). Aim: To explore differences in DNSEP between patients with primary premature ejaculation (PPE) and those with secondary premature ejaculation (SPE), in order to investigate the clinical value of DNSEP in the diagnosis of PE. Methods: The participants were divided into a PPE group (34 cases), an SPE group (25 cases) and a healthy control group (18 cases). All participants underwent DNSEP testing, and the latencies and amplitudes of DNSEP were recorded. Outcomes: Differences in the latencies and amplitudes of DNSEP were compared among the PPE, SPE, and healthy control groups. RESULTS: The latencies of DNSEP in the PPE and SPE groups were shorter than those in the healthy control group, and these differences were statistically significant ( P < 0.01). However, there was no statistically significant difference between the PPE and SPE groups ( P > 0.05). The amplitudes of DNSEP in the PPE group were significantly higher than those in the healthy control group ( P < 0.01). However, the amplitudes of DNSEP in the SPE group were significantly lower than those in the healthy control group ( P < 0.05). Clinical Implications: PPE and SPE can be differentiated based on differences in the amplitudes of DNSEP, providing an objective basis for treatments and follow-up examinations. Strengths and Limitations: We evaluated differences in the amplitudes of DNSEP between PPE and SPE patients, which were rare in the published literature. However, specific causes of these differences are still unclear. SEP only reflects afferent pathways in the ejaculatory reflex arc, and role of the brain as a higher center should not be ignored. CONCLUSION: Both PPE and SPE patients are characterized by an increased excitability of the penile sensory nerves.